The role of brain oscillations in post-stroke motor recovery: An overview - Leonardi, Giulia; Ciurleo, Rosella; Cucinotta, Francesca; Fonti, Bartolo; Borzelli, Daniele; Costa, Lara; Tisano, Adriana; Portaro, Simona; Alito, Angelo (Frontiers in Systems Neuroscience, 2022)
Stroke is the second cause of disability and death worldwide, highly impacting patient’s quality of life. Several changes in brain architecture and function led by stroke can be disclosed by neurophysiological techniques. Specifically, electroencephalogram (EEG) is able to disclose brain oscillatory rhythms which can be considered as a possible outcome measure for stroke recovery, and potentially shaped by neuromodulation techniques. We performed a review of randomised controlled trials on the role of brain oscillations in post-stroke patients searching the following databases: Pubmed, Scopus and Web of Science, from 2012 to 2022. Thirteen studies involving 346 patients in total were included. Patients in the control groups received various treatments (sham or different stimulation modality) in different post-stroke phases. This review describes the state of the art on the existing randomised controlled trials evaluating post-stroke motor function recovery after conventional rehabilitation treatment associated with neuromodulation techniques. Moreover, the role of brain pattern rhythms to modulate cortical excitability has been analysed. To date, neuromodulation approaches could be considered a valid tool to improve stroke rehabilitation outcomes, despite more high-quality and homogeneous randomised clinical trials are needed to determine to which extent motor functional impairment after stroke can be improved by neuromodulation approaches and which one could provide better functional outcomes. However, the high reproducibility of brain oscillatory rhythms could be considered a promising predictive outcome measure applicable to evaluate stroke patients recovery after rehabilitation.